A Novel Homozygous JAK3 Mutation Leading to T-B+NK– SCID in Two Brazilian Patients - Barreiros, Lucila A.; Segundo, Gesmar R. S.; Grumach, Anete S.; Roxo-Júnior, Pérsio; Torgerson, Troy R.; Ochs, Hans D.; Condino-Neto, Antonio (Frontiers in Pediatrics, 2018)
We report a novel JAK3 mutation in two female Brazilian SCID infants from two unrelated kindreds. Patient 1 was referred at 2 months of age due to a family history of immunodeficiency and the appearance of a facial rash. The infant was screened for TRECs (T-cell receptor excision circles) and KRECs (kappa-deleting recombination excision circles) for the assessment of newly formed naïve T and B cells respectively, which showed undetectable TRECs and normal numbers of KRECs. Lymphocyte immunophenotyping by flow cytometry confirmed the screening results, revealing a T-B+NK- SCID. The patient underwent successful HSCT. Patient 2 was admitted to an intensive care unit at 8 months of age with severe pneumonia, BCGosis and oral moniliasis; she also had a positive family history for SCID but newborn screening was not performed at birth. At 10 months of age she was diagnosed as a T-B+NK- SCID and underwent successful HSCT. JAK3 sequencing revealed the same homozygous missense mutation, c.2350G>A. This mutation affects the last nucleotide of exon 17 and it is predicted to disrupt the donor splice site. cDNA sequencing revealed skipping of exon 17 missing in both patients, confirming the predicted effect on mRNA splicing. Skipping of exon 17 leads to an out of frame deletion of 151 nucleotides, frameshift and creation of a new stop codon 60 amino acids downstream of the mutation resulting in a truncated nonfunctional protein.